The Shoup Tax System and the Postwar Development of the Japanese Economy - Kaizuka, Keimei (American Economic Review, 2016)
The Shoup Mission of 1949-1950 proposed a radical reform of Japan's tax system, even more far-reaching than the earlier changes made by Occupation authorities. These postwar changes were radical in the sense that they introduced the idea of comprehensive income taxation in place of a system that had been schedular and had only a partial tax base. Although income taxes had become the major revenue source during the war, before then revenue had been primarily from indirect taxes (particularly those on tobacco and liquor). Thus, the tax climate in the late 1940's was foreign to the idea of comprehensive income taxation in the sense that even tax experts were not familiar with the idea, and ordinary people, while conscious of a heavy tax burden, had not given much thought to the issue of equity.'